Islamic Education Policy in the Digital Age: Prospects and Difficulties - Indrawan, Irjus; Maimunah, Maimunah; Asmariani, Asmariani; Suryani, Suryani; Murtopo, Ali (CV. Zabags Qu Publish, 2024)
The purpose of this study was to find out which public universities offer Islamic religious education. This essay takes a qualitative approach to its analysis. Data were gathered using research techniques from libraries. Finding pertinent literary materials, including books, articles, and online publications, as well as scientific research, that address Islamic education in the digital era was the first step in the study. Additionally, the best sources of information were chosen for the research topic. The study's findings suggest that the following subjects are covered in Islamic Religious Education in Public Universities: The topics covered include Humans and Religion, Islamic Religion, Islamic Religion's Sources, Islamic Teachings' Basic Framework, Aqidah, Sharia, Worship, Mu'amalah, Morals, Piety, Knowledge in Islam, and Islamic Science Discipline. Islamic religious education is taught as a general foundations course in public universities, and it plays a vital role in the process of imparting knowledge as well as changing students' attitudes and behaviors.